No free rides: Winners and losers of the proposed Toronto Transit Commission U-Pass program. (September 2020) - Butler, Alex; Sweet, Matthias
Abstract: This paper explores the financial gains and losses for university students in Toronto, Ontario as a result of the U-Pass proposed by the Toronto Transit Commission (TTC). The proposed program was subsequently not implemented in concert with a broader initiative by the Ontario government to reduce mandatory student fees in universities. Based on the proposal, should a student body adopt the U-Pass through majority vote, the program would have offered students unlimited travel on the TTC for $70 per month to be funded through fees paid by all students enrolled in a participating university. Toronto already has high student transit ridership and fares are not integrated across municipal boundaries, setting a context in which a U-Pass would be expected to impact different students in different ways. This study uses data from the 2015 StudentMoveTO survey to estimate the redistribution of resources among students across different campuses, commute modes, and geographies. Generally, students that benefit live within the City of Toronto and use TTC to get to school, while those expected to experience welfare losses either live outside of Toronto or live close enough to their campus to walk or bike to school. The U-Pass program design implies a goal of shifting from market-based equity (each student paying for his or her own transit fares) towards equity of opportunity (each student having equal opportunity to use TTC). This contemplated shift away from market-based understandings of equity also appears to underscore why the program was nor implemented as part of a broader initiative by the provincial government to reduce mandatory university fees. Highlights: StudentMoveTO data from 2015 is used to identify the redistributive implications of a proposed U-Pass program for students at Toronto universities. Models using data from 7298 Toronto university students are used to explore benefits from a U-Pass program under alternative policy scenarios. The U-Pass program benefits students modestly and redistributes resources among students and between students and the transit operator. The U-Pass program represents a shift from market-based to opportunity-based justice,  ultimately playing a role in the program not being implemented.